161k views
0 votes
Solve by substitution
y=2x-3
-x-8y=7

User Pollaris
by
4.8k points

1 Answer

6 votes

Answer & Step-by-step explanation:

y = 2x - 3

-x - 8y = 7

Since, we have a equation for y, then we can substitute this equation for y to solve for x.

-x - 8(2x -3) = 7

-x - 16x + 24 = 7

-17x + 24 = 7

-17x = -17

x = 1

So, since we know that x is equal to 1, then we can plug in this number for the equation of y to find y.

y = 2(1) - 3

y = 2 - 3

y = -1

So, the solution is (1, -1). X equals 1 and y equals -1.

User Shabar
by
5.6k points